Cancer-Specific Loss of p53 Leads to a Modulation of Myeloid and T Cell Responses - Blagih, Julianna; Zani, Fabio; Chakravarty, Probir; Hennequart, Marc; Pilley, Steven; Hobor, Sebastijan; Hock, Andreas K.; Walton, Josephine B.; Morton, Jennifer P.; Gronroos, Eva; Mason, Susan; Yang, Ming; et al. (Cell reports (Cambridge), 2020)
Loss of p53 function contributes to the development of many cancers. While cell-autonomous consequences of p53 mutation have been studied extensively, the role of p53 in regulating the anti-tumor immune response is still poorly understood. Here, we show that loss of p53 in cancer cells modulates the tumor-immune landscape to circumvent immune destruction. Deletion of p53 promotes the recruitment and instruction of suppressive myeloid CD11b+ cells, in part through increased expression of CXCR3/CCR2-associated chemokines and macrophage colony-stimulating factor (M-CSF), and attenuates the CD4+ T helper 1 (Th1) and CD8+ T cell responses in vivo. p53-null tumors also show an accumulation of suppressive regulatory T (Treg) cells. Finally, we show that two key drivers of tumorigenesis, activation of KRAS and deletion of p53, cooperate to promote immune tolerance. [Display omitted] •Tumor-specific loss of p53 delays tumor rejection in immune-competent hosts•p53 loss increases myeloid infiltration through enhanced cytokine secretion•The increase in Treg cells in response to loss of p53 is independent of Kras mutation•Kras mutations coordinate with p53 loss to regulate myeloid recruitment TP53 is one of the most frequently mutated genes in cancer; however, its significance in controlling tumor-immune crosstalk is not fully understood. Blagih et al. highlight a key role for tumor-associated loss of p53, a common oncogenic event, in regulating myeloid and T cell responses.